Effects of Pleural Effusion on Respiratory Function - I Mitrouska; M Klimathianaki; NM Siafakas (Canadian Respiratory Journal)
The accumulation of pleural effusion has important effects on respiratory system function. It changes the elastic equilibrium volumes of the lung and chest wall, resulting in a restrictive ventilatory effect, chest wall expansion and reduced efficiency of the inspiratory muscles. The magnitude of these alterations depends on the pleural fluid volume and the underlying disease of the respiratory system. The decrease in lung volume is associated with hypoxemia mainly due to an increase in right to left shunt. The drainage of pleural fluid results in an increase in lung volume that is considerably less than the amount of aspirated fluid, while hypoxemia is not readily reversible upon fluid aspiration.